About knowledge on History of Art on the internet: profane, specialized and documental writings - DOI: 10.3395/reciis.v3i3.281en - Gérard Régimbeau (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
To approach the present state of affairs concerning the mediation of knowledges on History of Art on the internet, this paper proposes to observe, by means of case analysis, the characteristics of three writings: profane, specialized and documental writings. This approach considers the characters and enunciative contexts of each one in a sociosemiotic perspective, which makes it possible to cross knowledge and informational and communicational practices, so as to study how the interdependence between support and medium is built.